Associations between serum antibodies to periodontal pathogens and preclinical phases of rheumatoid arthritis. (29th January 2021) - Manoil, Daniel; Courvoisier, Delphine S; Gilbert, Benoit; Möller, Burkhard; Walker, Ulrich A; Muehlenen, Ines Von; Rubbert-Roth, Andrea; Finckh, Axel; Bostanci, Nagihan
Abstract: Objectives: To examine whether serum antibodies against selected periodontal pathogens are associated with early symptoms of RA development in healthy individuals at risk of developing the disease. Methods: Within an ongoing study cohort of first-degree relatives of patients with RA (RA-FDRs), we selected four groups corresponding to specific preclinical phases of RA development ( n = 201). (i) RA-FDR controls without signs and symptoms of arthritis nor RA-related autoimmunity ( n = 51); (ii) RA-FDRs with RA-related autoimmunity ( n = 51); (iii) RA-FDRs with inflammatory arthralgias without clinical arthritis ( n = 51); and (iv) RA-FDRs who have presented at least one swollen joint ('unclassified arthritis') ( n = 48). Groups were matched for smoking, age, sex and shared epitope status. The primary outcome was IgG serum levels against five selected periodontal pathogens and one commensal oral species assessed using validated-in-house ELISA assays. Associations between IgG measurements and preclinical phases of RA development were examined using Kruskal–Wallis or Mann–Whitney tests (α = 0.05). Results: None of the IgGs directed against individual periodontal pathogens significantly differed between the four groups of RA-FDRs. Further analyses of cumulated IgG levels into bacterial clusters representative of periodontal infections revealed significantly higher IgG titres against periodontopathogens in anti-citrullinated protein antibodies (ACPA)-positive RA-FDRs ( P = 0.015). Current smoking displayed a marked trend towards reduced IgG titres against periodontopathogens. Conclusion: Our results do not suggest an association between serum IgG titres against individual periodontal pathogens and specific preclinical phases of RA development. However, associations between cumulative IgG titres against periodontopathogens and the presence of ACPAs suggest a synergistic contribution of periodontopathogens to ACPA development.